Octopamine alters yellow mealworm body composition - V. Hill; L. Williams; A. Salter; J. Brameld; T. Parr (Animal)
There is the potential to increase the production yield within the emerging insect industry in order to produce high-quality, sustainable protein. In invertebrates, the monoamine, octopamine (OA), has a similar role to that of noradrenaline in mammals. Beta-2 adrenergic agonists increase protein and decrease fat deposition in mammals, thereby inducing favourable changes in body composition. We hypothesised that OA would have similar effects in insects. Tenebrio molitor larvae, commonly called yellow mealworms, were fed for 35 days on either control wheat bran or wheat bran containing OA at 5 μg OA/g. There were trends for treatment × time interactions for mealworm group weight (P = 0.075) and individual mealworm weight (P = 0.069), with the OA group becoming heavier/bigger after 18 days. In addition, there was a trend for a treatment × time interaction on cumulative pupation (P = 0.099), with OA−treated mealworms having delayed pupation. After 35 days of OA treatment, there were significant effects on mealworm final body proximate nutrient composition on a DM basis, with fat content being significantly decreased (by 8%, P = 0.006), whilst CP was significantly increased (by 6%, P = 0.019) in OA−treated mealworms compared to control. There was little effect of OA on the fatty acid composition of the mealworms, with small reductions in palmitoleic acid (P < 0.001) and oleic acid (P = 0.082). Despite a significant increase in protein content with OA treatment, SDS-PAGE did not reveal any changes in the proteins being expressed. Hence, OA treatment of mealworms resulted in an increase in the proportion of protein and a decrease in fat, demonstrating that mealworm nutrient composition can potentially be manipulated to provide a higher−value feed ingredient.